Overmedicalization of young people’s distress is undermining and disempowering families - Fergusson, E; Reed-Purvis, S; Foulkes, L (Springer Nature, 2023)
Cases of mild or transient distress in young people are increasingly viewed as problems that require medical intervention. As CAMHS clinicians, we argue that this overmedicalization undermines the value of social support within the family and community, and funding cuts to nonmedical support services have only compounded the problem.